Innate Immunity in Systemic Sclerosis Fibrosis: Recent Advances - Laurent, Paoline; Sisirak, Vanja; Lazaro, Estibaliz; Richez, Christophe; Duffau, Pierre; Blanco, Patrick; Truchetet, Marie-Elise; Contin-Bordes, Cécile (Frontiers in Immunology, 2018)
Systemic sclerosis (SSc) is a heterogeneous autoimmune disease associating three interconnected hallmarks (i) vasculopathy (ii) immune abnormalities (iii) fibroblast dysfunction leading to extracellular matrix deposition and fibrosis. Blocking or reversing the fibrotic process associated with this devastating disease is still an unmet medical need. Innate immunity, with in particular macrophages and type I IFN, has been suspected to be involved in SSc for many years, however the underlying cellular and molecular mechanisms of innate immune contribution to SSc pathogenesis are far from being elucidated yet. During the past 5 years, studies have shed light on the implication of new players, such as Toll like receptors (TLR), platelet-derived Danger Associated Molecular Patterns (DAMPS), Innate Lymphoid Cells (ILC) and plasmacytoid dendritic cells (pDC) in the pathophysiology of SSc, including vasculopathy and fibrosis. In this review, we describe the recent evidence highlighting the importance of innate immune processes throughout SSc development, with the particular emphasis on the initiation of the pathology. We also discuss the potential therapeutic options to modulate innate immune cells or signaling in SSc that are emerging from these recent advances.